Peer support programme among ambulance personnel: job satisfaction, health and support - Oliveira,Ana (2021)
Abstract Prehospital emergency entails challenges, risks and exposure to potential traumatic events. Social support is broadly recognized as a protective factor for mental health, especially in stressful conditions. Peer support has been pointed out as a promising approach to be used in high-risk contexts, such as emergency services. However, there is a lack of research about its effectiveness. This study evaluates the impact of a peer support programme on the job satisfaction, general health and well-being, as well as perceived social support of ambulance personnel. This is a quasi-experimental study, with a pre-test evaluation, followed by the intervention and a post-test evaluation. Fifty-three ambulance personnel participated in this study as part of a peer support providers group, an experimental group or a control group. We found significant differences between groups after the peer support programme, with the experimental group and the peers group showing better results. The within-group analysis showed that those who received support from colleagues report better scores on the post-test for perceived organizational support; and those who provided support reported better values of general health and psychological well-being after intervention. This study highlights the added value that peer support interventions seem to bring both to ambulance personnel and to organizations.